Effects of digital processing on repeatability assessment of a multiple reaction monitoring liquid chromatography–tandem mass spectrometry system by ISO 11843‐7. (8th August 2022) - Machida, Koichi; Kotani, Akira; Hayashi, Yuzuru; Hakamata, Hideki
Abstract: ISO 11843 part 7 (ISO 11843‐7) can provide a standard deviation (SD) of area measurements of a target peak through the stochastic behaviors of instrumental noises. The purpose of this study is to demonstrate that ISO 11843‐7 can be applied to assess repeatability in an isocratic liquid chromatography–tandem mass spectrometry (LC–MS/MS) system without repetitive measurements. The relative standard deviation (RSD) of the peak area of ergosterol picolinyl ester, which was used as an example, on a multiple reaction monitoring (MRM) chromatogram was determined by ISO 11843‐7. The RSD by ISO 11843‐7 ( N  = 1) was within a 95% confidence band of the RSD by repetitive measurements ( N  = 6). Moreover, the effects of digital smoothing, such as moving average, were also examined on the repeatability assessment in LC–MS/MS by ISO 11843‐7. From the results of the comparisons of the RSDs obtained by ISO 11843‐7 and the repetitive measurements, it was shown that suitable RSDs of the peak area were obtained from the smoothed MRM chromatograms by the moving average for narrow data point windows (e.g., one‐sixth of the peak width). In conclusion, the utility of repeatability assessment based on ISO 11843‐7 has been expanded for the validation of an LC–MS/MS system.